2022
DOI: 10.3390/polym14163243
|View full text |Cite
|
Sign up to set email alerts
|

Strain-Field Modifications in the Surroundings of Impact Damage of Carbon/Epoxy Laminate

Abstract: The relationship between deformation and stress is crucial for any elasto-plastic body. This paper deals with the experimental identification of the basic parameters of the composite laminate model in relation to the finite element model. Standardized tensile, impact, and post-impact tests on a carbon fiber-reinforced epoxy laminate were used. The method by which the elasticity and failure parameters were obtained from the initial components is described. In the article, the modes of initiation and complete fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Carbon fiber foam core structure had high specific strength and specific stiffness, good stability, corrosion resistance, structural designability and other excellent properties. It was widely used in the industrial sector [1][2][3]. However, in the daily use and maintenance process, it was often subjected to low-energy impacts from various external objects such as hailstones and maintenance tools, resulting in damage and causing significant performance degradation [4].…”
Section: Introductionmentioning
confidence: 99%
“…Carbon fiber foam core structure had high specific strength and specific stiffness, good stability, corrosion resistance, structural designability and other excellent properties. It was widely used in the industrial sector [1][2][3]. However, in the daily use and maintenance process, it was often subjected to low-energy impacts from various external objects such as hailstones and maintenance tools, resulting in damage and causing significant performance degradation [4].…”
Section: Introductionmentioning
confidence: 99%
“…The results exhibit that the composite has good puncture resistance, the interlayer structure dissipates puncture energy to a certain extent, and the LMPET layer avoids the sliding of the filament during the needle punching process, thus improving the overall mechanical properties of the laminated composite. Due to excellent high strength and high modulus, carbon fiber (Samal et al ., 2016a, b; Samal, 2022; Vlach et al ., 2022a, b) is also widely used as an interlayer reinforcement to enhance the mechanical properties of composites. Another way is to enhance the static puncture resistance of materials by structural design and optimization.…”
Section: Introductionmentioning
confidence: 99%
“…The delamination propagation path first extends along the width direction to the center, and then along the length direction [ 25 , 26 ]. Further research showed that the damage is layer-dependent in a laminate, and different fiber materials influence the delamination resistance in different ways [ 27 , 28 , 29 ]. The closer the delamination is to the surface, the lower the bearing capacity of the specimen, and the easier it is for interface cracking, interlaminar cracking, and fiber fracture to occur.…”
Section: Introductionmentioning
confidence: 99%